Developmental proactivity and professional ability as older workers' employability resources: A longitudinal study explaining career events - Conny Roobol; Hans Pruijt; Ferry Koster; Fenna Ruby Marie Leijten (International Journal of Business Science & Applied Management (IJBSAM), 2021)
This four-year longitudinal study examines how two facets of employability - professional ability and developmental proactivity - are linked to career events among workers ages 45 years and older. We construe employability as a personal resource that predicts a higher likelihood of experiencing positive career events and a lower likelihood of experiencing negative ones. Results reveal that developmental proactivity leads to a higher probability of internal promotion, while professional ability leads to a lower probability of salary loss, demotion, and unemployment. The findings indicate that these two facets of employability can offer critical insights for understanding the career events of older workers.
Keywords: 650; employability; personal resources; career resources; longitudinal design; older workers